Estudio y diseño del sistema de agua potable, alcantarillado sanitario y pluvial de la lotización INTISSAR, del Cantón Santa Rosa, provincia de el Oro - Segarra Baldeon, Johnny Fernando (2015)
This design project has been developed to reduce health problems in the Allotment intissar, located in the Santa Rosa - Bellavista - The Advanced, belonging to Santa Rosa Canton of the Province of El Oro, and determine the standards and technical characteristics to be used in the design. The project has approximately 585 lots with an area of ​​20.0 ha., Is a relatively flat area with small slopes, with a warm and humid climate, and with a future population of 2168 inhabitants. The first methodology used was the socio-economic survey, consultation on the internet, and three test pits were also conducted in strategic locations in the area to carry out the studies, the first test pit was extracted in settlements housing, the second test pit was taken by where they will spend the manholes, and the third test pit was the extracted (in) where the final discharge pipe of our project was connected with one of the wells, leading wastewater to the oxidation pond, and these tests were : moisture content, consistency limits, Unified soil Classification System (USCS), particle size analysis, AASHTO, Permeability, and cut resistance in the soil laboratory of the Faculty of Civil Engineering. Uptake of Drinking Water for Allotment intissar, will be the Main ductile iron pipe 600mm, passing via the Sta Rosa -. Bellavista. The average daily flow at end of period design (QMD) is 6.432 l / s, the maximum daily flow (QMD) is 8,362 l / s, and the maximum required for Allotment hourly flow (QMH) is 12,865 lt / s ≈ 12.90 lt / s The sanitary sewer system is an open and independent to the storm drains, with an area of ​​20 hectares contribution. The minimum slope used in the calculation is 2/1000, avoiding sedimentation of debris in the pipeline. Discharge and treatment of wastewater is the place in the oxidation pond Bellavista, which features two pools, lagoon # 1 with an area of ​​0.17HAS, and lagoon # 2 with an area of ​​0.08HAS within a land with an area of ​​0.84HAS, leaving a free area 0.59HAS.